Legal Liability of Doctors on the Disclosure Medical Secrecy for Covid-19 Patients in the Pandemic Era - Jaufan Fata Almadani; Andika Persada Putera; Yulianto (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2021)
The Covid-19 outbreak is a disease that attack countries around the world, no exception in Indonesia. The discourse of revealing the secrecy of positive Covid-19 patient medicine raises pros and cons in society. This study aims to analyze the concept of medical secrecy according to statutory regulations and legal liability of doctors in revealing medical secrecy in the pandemic era. This study uses a normative juridical method with a statutory approach, and a conceptual approach. The source of data collection consists of primary, secondary, and tertiary legal material. The results of the research show that medical secrecy is confidential individual right. The identity of Covid-19 patients can be accessed in a limited manner by authorized institutions and used proportionally and appropriately for the benefit of handling the Covid-19 outbreak. In order to anticipate an increase in Covid-19 transmission, the practice of using patient personal data is implemented by several countries according to principles proporsionalitas, necesssitas and purposive limitation.